2014
DOI: 10.1371/journal.pone.0112485
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Inducible Kinase 1 (SIK1) Is Induced by Gastrin and Inhibits Migration of Gastric Adenocarcinoma Cells

Abstract: Salt-inducible kinase 1 (SIK1/Snf1lk) belongs to the AMP-activated protein kinase (AMPK) family of kinases, all of which play major roles in regulating metabolism and cell growth. Recent studies have shown that reduced levels of SIK1 are associated with poor outcome in cancers, and that this involves an invasive cellular phenotype with increased metastatic potential. However, the molecular mechanism(s) regulated by SIK1 in cancer cells is not well explored. The peptide hormone gastrin regulates cellular proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…The xCELLigence® DP system (Roche Diagnostics GmbH, Germany) was used to study migration as previously described [25]. Briefly, AGS-Gr cells were seeded into (5.0 x 10 4 cells/well) the CIM-Plate 16 (Roche).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The xCELLigence® DP system (Roche Diagnostics GmbH, Germany) was used to study migration as previously described [25]. Briefly, AGS-Gr cells were seeded into (5.0 x 10 4 cells/well) the CIM-Plate 16 (Roche).…”
Section: Methodsmentioning
confidence: 99%
“…Since the data suggests that gastrin induces autophagy, we asked if this involves the activation of ULK1. We have recently demonstrated that gastrin induces STK11 Ser 428 phosphorylation in AGS-Gr and MKN45 cells [25], indicating that the STK11-PRKAA2-ULK1 signalling pathway might be involved in gastrin mediated induction of autophagy. Thus, we treated cells with gastrin and examined the phosphorylation of PRKAA2 by immunoblotting.…”
Section: Gastrin Activates the Stk11–prkaa2-ulk1 Signaling Pathwaymentioning
confidence: 99%
“…Reports on the role of NUAK2 in tumours of different origin vary: in melanoma, NUAK2 (SNARK) levels correlate negatively with patient survival ( Namiki et al , 2011 ), whereas in ovarian cancer patients, an opposite trend was reported ( Emmanuel et al , 2011 ). SIK1, SIK2 (QIK) and SIK3 (QSK) have been reported to have a role in metastasis in gastric ADCs ( Selvik et al , 2014 ) and mitotic progression in prostate and ovarian cancers ( Ahmed et al , 2010 ; Chen et al , 2014 ; Bon et al , 2015 ). Additionally, SIK1 was shown to be required for P53-dependent anoikis, and RNAi-mediated gene silencing of SIK1 resulted in increased lung micrometastases in xenografts injected with transformed human mammary epithelial cells.…”
Section: Lkb1 Substrates – the Potential Of Old And New Therapeutic Tmentioning
confidence: 99%
“…In human hepatocellular carcinoma (HCC), SIK1 markedly inhibited EMT, tumor growth and metastasis and provided a potential new candidate for HCC therapy (28). Reduced expression of SIK1 was also identified to be associated with poor outcomes in gastric carcinoma (19). Furthermore, SIK1 could be the potential target for numerous miRs.…”
Section: Discussionmentioning
confidence: 99%
“…In non-small cell lung cancer, downregulation of SIK1 enhances epithelial-mesenchymal transition (EMT) and radioresistance (18). In addition, induced SIK1 expression has been reported to inhibit gastric cancer cell migration (19). However, the functional role of SIK1 in melanoma remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%